Pay clauses in public procurement: The wage impact of collective bargaining compliance laws in Germany - Vinzenz Pyka (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2025)
Using administrative data from Germany, this study provides first evidence on the wage effects of collective bargaining compliance laws. These laws require establishments receiving public contracts to pay wages set by a representative collective agreement, even if they are not formally bound by one. Leveraging variation in the timing of law implementation across federal states, and focusing on the public transport sector - where regulation is uniform and demand is driven solely by state-level needs - I estimate dynamic treatment effects using event-study designs. The results indicate that within five years of the law's implementation, wage increases were on average 2.9 to 4.6 per cent higher in federal states with such a law compared to those without one - but only in East Germany. These findings highlight the potential for securing collectively agreed wages in times of declining collective bargaining coverage. – – Ich nutze administrative Daten aus Deutschland und liefere erstmals empirische Evidenz zu den Lohneffekten von Tariftreuegesetzen. Diese Gesetze verpflichten Unternehmen, die öffentliche Aufträge erhalten, ihre Beschäftigten nach einem repräsentativen Tarifvertrag zu entlohnen - auch wenn sie selbst nicht tarifgebunden sind. Auf Grundlage der Gesetzeseinführungen in den Bundesländern analysiere ich mithilfe von Event-Study-Modellen die Lohnentwicklung von Beschäftigten im öffentlichen Nahverkehr. Dieser Sektor eignet sich besonders gut zur Evaluation, da er bundesweit einheitlich reguliert ist und die Nachfrage ausschließlich durch den Staat bestimmt wird. Die Ergebnisse zeigen, dass in Bundesländern mit einem Tariftreuegesetz die Löhne ceteris paribus im Durchschnitt innerhalb von fünf Jahren nach der Einführung um 2,9 bis 4,6 Prozent stärker gestiegen sind als in Bundesländern ohne Tariftreuegesetz - allerdings nur in Ostdeutschland. Dies legt nahe, dass ein Bundestariftreuegesetz beitragen könnte, Tariflöhne angesichts einer sinkenden Tarifbindung zu sichern.
Keywords: J31; J38; J51; J53; J58; 330; collective bargaining; pay clauses; public procurement; trade unions